Long-term effectiveness of immersive VR simulations in undergraduate science learning: lessons from a media-comparison study - Prajakt Pande; Amalie Thit; Anja Elaine Sørensen; Biljana Mojsoska; Morten E. Moeller; Per Meyer Jepsen (Association for Learning Technology, 2021)
Our main goal was to investigate if and how using multiple immersive virtual reality (iVR) simulations and their video playback, in a science course, affects student learning over time. We conducted a longitudinal study, in ecological settings, at an undergraduate field-course on three topics in environmental biology. Twenty-eight undergraduates were randomly assigned to either an iVR-interaction group or a video-viewing group. During the field-course, the iVR group interacted with a head-mounted device-based iVR simulation related to each topic (i.e. total three interventions), while the video group watched a pre-recorded video of the respective simulation on a laptop. Cognitive and affective data were collected through the following checkpoints: a pre-test before the first intervention, one topic-specific post-test immediately after each intervention, a final post-test towards the end of the course, and a longitudinal post-test deployed approximately 2 months after the course. Through a descriptive analysis, it was found that student performance on the knowledge tests increased considerably over time for the iVR group but remained unchanged for the video group. While no within- or between-group differences were noted for intrinsic motivation and self-efficacy measures, students in the iVR group enjoyed all the simulations, and perceived themselves to benefit from those simulations.